Pengaruh Persepsi Pemilik Dan Pengetahuan Akuntansi Pelaku Usaha Mikro Kecil Dan Manengah Terhadap Penggunaan Informasi Akuntansi (Studi Kasus Pada Pelaku UMKM Di Kecamatan Galang, Kabupaten Deli Serdang) - Rizqia Humaira Nasution; Nur Ahmadi Bi Rahmani; Laylan Syafina (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research aims to determine the influence of owner perceptions and accounting knowledge on the use of accounting information among MSMEs in Galang District, Deli Serdang Regency. This research uses quantitative methods and an associative approach, data collection techniques using questionnaires and the sample in this research was 91 MSMEs in Galang District using purposive sampling techniques. Data were analyzed using the multiple linear regression method with SPSS version 25. The partial results of this research (t test) showed that the owner's perception variable and the accounting knowledge variable had an influence on the use of accounting information. And simultaneously (F test) shows that the owner's perception and accounting knowledge jointly influence the use of accounting information among MSMEs in Galang District, Deli Serdang Regency.